Clinical analysis and functional characterization of KCNQ2-related developmental and epileptic encephalopathy - Ye, Jia; Tang, Siyang; Miao, Pu; Gong, Zhefeng; Shu, Qiang; Feng, Jianhua; Li, Yuezhou (Frontiers in Molecular Neuroscience, 2023)
Background Developmental and epileptic encephalopathy (DEE) is a condition characterized by severe seizures and a range of developmental impairments. Pathogenic variants in KCNQ2, encoding for potassium channel subunit, cause KCNQ2-related DEE. This study aimed to examine the relationships between genotype and phenotype in KCNQ2-related DEE. Methods In total, 12 patients were enrolled in this study for genetic testing, clinical analysis, and developmental evaluation. Pathogenic variants of KCNQ2 were characterized through a whole-cell electrophysiological recording expressed in Chinese hamster ovary (CHO) cells. The expression levels of the KCNQ2 subunit and its localization at the plasma membrane were determined using Western blot analysis. Results Seizures were detected in all patients. All DEE patients showed evidence of developmental delay. In total, 11 de novo KCNQ2 variants were identified, including 10 missense variants from DEE patients and one truncating variant from a patient with self-limited neonatal epilepsy (SeLNE). All variants were found to be loss of function through analysis of M-currents using patch-clamp recordings. The functional impact of variants on M-current in heteromericKCNQ2/3 channels may be associated with the severity of developmental disorders in DEE. The variants with dominant-negative effects in heteromeric channels may be responsible for the profound developmental phenotype. Conclusion The mechanism underlying KCNQ2-related DEE involves a reduction of the M-current through dominant-negative effects, and the severity of developmental disorders in DEE may be predicted by the impact of variants on the M-current of heteromericKCNQ2/3 channels.